Solid state fermentation of sago starch by aspergillus niger ITV-01 - Goh, Cindy Poh Hsin (Universiti Malaysia Sarawak, (UNIMAS), 2015)
This project was carried out to evaluate the effects of incubation temperature, pH, initial moisture content and time during solid state fermentation (SSF) of sago starch to produce glucose. The strains used were Aspergillus niger lTV-Oland Aspergillus niger PAN 1. Sago starch was subjected to SSF, using both A. niger ITV-Ol and A. niger PANI incubated at three temperature (30, 35, and 40 0c), three pH level (3, 4, and 5), two initial moisture contents (70% and 80%) and at five time intervals (2, 4, 6, 8, and 10 days). Accordingly, the glucose concentration produced while SSF was quantified. Results showed that glucose production by A. niger ITV-Ol was significantly higher at 30 °C, at pH 3, 80% initial moisture content and at incubation time of 8 days accordingly. However, A. niger PANI was better under the same conditions except in the pH values of 5. The results also indicate that temperature, pH, initial moisture content and incubation time are important factors to consider during SSF with A. niger spp. In conclude, based on the results of this study, A. niger PAN 1 is better in glucose production than A. niger lTV-01 on the sago starch substrates.